Efektivitas Pengelolaan Limbah dalam Rangka Optimalisasi Biaya Produksi Batik Giriloyo - Shapna Citra Dewi; Heri Prabowo; Sapto Budoyo; Agus Sutono (Lembaga Pengembangan Kinerja Dosen, 2025)
This activity aims to analyze the effectiveness of waste management in optimizing production costs in the Giriloyo Batik industry, located in Yogyakarta, Indonesia. As a center for traditional batik production, Giriloyo faces environmental challenges due to the liquid waste generated from the dyeing process. This community service activity introduced hybrid constructed wetland technology as an environmentally friendly and cost-effective solution. Methods used included field observations, interviews with local artisans, and a comparative cost analysis before and after system implementation. The results showed a 30% reduction in monthly waste management costs and a significant improvement in wastewater quality, in accordance with environmental standards. Furthermore, this program increased community awareness and participation in sustainable production practices. Effective waste management not only reduces operational costs but also strengthens the long-term environmental responsibility of the small-scale batik industry. By integrating technology with community involvement, the program provides a sustainable model for waste management in similar artisanal sectors, contributing to both economic and environmental benefits.